Aplikasi Kehadiran Mengajar Dosen Berbasis Website Pada Fakultas Ilmu Komputer Universitas Sriwijaya Dengan Menggunakan Metode Waterfall - Syuryani, Devita; Nuzulastri, Sari; Rezky, Faula (Journal of Information System Research (JOSH), 2024)
The process of recording lecturer attendance, which is one of the factors in teaching that must be recorded at each learning meeting, is carried out by lecturers and students directly (manually), by filling in the attendance list prepared by the admin staff of the study program. However, this process resulted in difficulties in the reporting process (recap of lecturer teaching attendance data) to be reported to the head of the study program, deputy dean for academic affairs. Attendance is a benchmark for determining the level of presence of lecturers in teaching at a university so that lectures can run well with activeness between lecturers and students who attend the lectures being held. To make it easier to create lecturer teaching attendance applications using the waterfall method and using web-based programming, namely PHP and MySQL. The application is created in accordance with the lecture schedule which functions as access control (schedule access control) to maintain order in taking attendance and make it easier for staff in the process of recording and monitoring lecturers' attendance and discipline in conducting lectures. Making this application serves to make it easier to record lecturer attendance and make it easier for study programs to monitor lecturer attendance. After using this attendance application, it makes it easier for lecturers to organize teaching time, as well as increasing the level of discipline for lecturers and making it easier for the lecturer performance assessment process carried out by the study program.